IMPROVING YEAR 4 PUPILS’ ABILITY TO SPELL COUNTABLE PLURAL FORMS OF NOUNS THROUGH THE USE OF ‘MAKE IT PLURAL’ (M.I.P) CHART - Amira Shahirah Lokman; Noraini binti Abdullah Sani (Proceedings of The ICECRS, 2016)
The lack of understanding and confusion on the basic rules of plural nouns faced by the pupils has greatly affected their ability to write correct spelling of the plural forms of the nouns. A research was conducted on 4 selected participants from Year 4 B of SK Z who obviously showed difficulties in applying appropriate spelling rules to form correct plural forms of the nouns. Hence, this action research was conducted to develop the pupils’ ability to spell the countable plural forms of the nouns correctly. A plural form chart named ‘Make It Plural’ Chart was used as the intervention to address this issue. Four lessons using the intervention with different focused in spelling rules of the plural nouns (‘-s’, ‘-es’, ‘-ies’ ‘-ves’) were implemented throughout this research in order to assist the pupils in improving their ability to spell the countable plural forms of the nouns correctly. The data for this study was collected through observation, the result of worksheets’ scores and the result of the pre-test and post-test. The results of the findings from three different sources showed that the use of ‘Make It Plural’ (M.I.P) Chart has significantly improved the participants’ ability to spell the countable plural forms of the nouns correctly. Discussion of the findings, reflection and suggestion for further research was highlighted in the last section of this article in order to develop more quality and comprehensive teaching and learning session in the future.